A new species of Enchytraeus (Enchytraeidae, Oligochaeta) from the profundal of Lake Van, the world's largest soda Lake (Turkey, East Anatolia) - Arslan, Nai̇me; Timm, Tarmo; Rojo, Verónica; Vizcaíno, Antón; Schmelz, Rüdiger M. (Zootaxa, 2018)
Enchytraeus polatdemiri sp. nov. (Enchytaeidae, Oligochaeta) was discovered in the framework of a sampling campaign of the benthic invertebrate fauna of the hyperalkaline Lake Van in Eastern Anatolia, Turkey, the third-largest closed lake and the largest soda lake on Earth. It was the only oligochaete species found in all samples. DNA sequencing included a fragment of the mitochondrial cytochrome c oxidase subunit I (COI) gene, and a fragment of the nuclear histone 3 (H3) gene. For comparison, specimens from laboratory cultures of E. albidus Henle, 1837, a widespread and morphologically similar species, were sequenced as well. The new species differs from E. albidus in comparatively small body size, 2 or 3 chaetae per bundle, saddle-shaped clitellum, absence of a copulatory field between the male pores and vasa deferentia usually not extending beyond the clitellum. The individual gene trees of COI and H3, as well as the combined phylogenetic analysis of both trees, recovered Enchytraeus polatdemiri sp. nov. as a monophyletic group within the genus Enchytraeus, closely related to E. albidus, but with an average p-distance for COI of 14.5 %. E. polatdemiri sp. nov. may have evolved from a local population of Enchytraeus albidus, a species well-adapted to changing salinity conditions, or from a common ancestor into an extremophile species that dwells and reproduces in the profundal of a strongly alkaline soda lake.